(untitled) (Research, Society and Development, 2023)
Intrabony radiopaque lesions are common manifestations of neoplasia, sequel of carious lesions, traumatic event, malignant tumors, metastasis, neoplastic and non-neoplastic entities or developmental alterations. Idiopathic Osteosclerosis (IO) is a rare bone lesion, normally asymptomatic and not associated with inflammatory, traumatic or infectious stimulus which is usually found in the molar mandibular area. Although IO is a well-recognized radiological entity that is generally symptom-free, it is important to distinguish it from other radiopacities. Finding this type of lesion in the mandibular condyle is odd and it could be easily misdiagnosed and confused with other imaging findings. The present case report aims to describe a rare imaging finding of idiopathic osteosclerosis in temporomandibular condyle which was accidentally found in the CBCT of a patient with painful TMD symptoms by emphasizing the importance of multidisciplinary involvement between the general practitioner, the radiologist and the pain specialist to diagnose and provide an indicated treatment, whenever necessary.